2008
DOI: 10.1186/1472-6831-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral health promotion for schoolchildren – evaluation of a pragmatic approach with emphasis on improving brushing skills

Abstract: Background: Preventive dentistry has traditionally emphasized improvement of oral hygiene. School-based programs, often delivered by dental hygienists or other health educators, are usually limited to dental knowledge provision. The present study focused on promotion of health behavior. The objectives were to evaluate the effect of a pragmatic educational program on tooth brushing skills of young schoolchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 13 publications
2
30
2
4
Order By: Relevance
“…These data are lower compared with data from Livny et al. 15 who reported that 67.2% of school‐children brushed once a day and only 8.2% had been taught by their dental team. Also in this study only a low number of children reported that they had learnt brushing from their dental team and the majority had learnt it from their parents.…”
Section: Discussioncontrasting
confidence: 69%
“…These data are lower compared with data from Livny et al. 15 who reported that 67.2% of school‐children brushed once a day and only 8.2% had been taught by their dental team. Also in this study only a low number of children reported that they had learnt brushing from their dental team and the majority had learnt it from their parents.…”
Section: Discussioncontrasting
confidence: 69%
“…1 Although this report does not explicitly discuss dental care, it is widely accepted that the timing of dental visits is important in preventing the onset and progression of dental caries, the most common chronic childhood disease in the United States. 2,3 Ensuring that children have earlier first dental visits—ideally by age 12 months, as recommended by the American Academy of Pediatric Dentistry 4 —optimizes the benefits associated with the establishment of a dental home, including the provision of caries risk assessments, 5 anticipatory guidance, 6–9 oral hygiene instruction, 10,11 dietary counseling, 12,13 and health education. 14,15 Earlier first dental visits also allow dentists to provide children at increased risk for caries with appropriate preventive dental care, such as pit and fissure sealants and topical fluoride treatments.…”
mentioning
confidence: 99%
“…En cuanto a la evaluación cuantitativa de la calidad del cepillado nuestro estudio coincide con los resultados obtenidos por otros investigadores (13,(15)(16)(17)(18)(19)(20) que confirman la utilidad de una intervención educativa al mostrar una evolución estadísticamente significativa en cuanto a la mejoría de la calidad del cepillado en los escolares.…”
Section: Discussionunclassified